(untitled) (The Pakistan Development Review, 2012)
“The answer to the question what is the mean of a given set of magnitudes cannot in general be found, unless there is given also the object for the sake of which a mean value is required. There are as many kinds of average as many purposes; and we may almost say in the matter of prices as many purposes as many writers.” Edgeworth (1888). We estimate standard errors (S.Es.) of month on month and year on year inflation in Pakistan based on data for the period of July 2001 to June 2010 using the stochastic approach as well as extended stochastic approach to index numbers. We develop a mechanism to estimate S.E. of period average headline inflation (rate) using these approaches. This mechanism is then applied to estimate S.Es. of 12-month average rate of inflation in Pakistan for July 2003 to June 2010. The systematic changes in the relative prices of different groups in the CPI basket for Pakistan are also estimated. The highest (positive) relative price inflation occurred in ‘food, beverages and tobacco’ group and the lowest (negative) for ‘recreation and entertainment’ group, during fiscal years 2001 to 2010. JEL classification: C13, C43, E31 Keywords: Estimation, Index Numbers, Inflation Rate, Standard Error